Successful conversion of complete atrioventricular block to sinus rhythm without cardiac pacemaker: A case report - Handy Darmawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Complete atrioventricular (AV) block is a medical emergency, which is related to cardiac arrest if left untreated. The insertion of permanent cardiac pacemaker is strongly indicated for its treatment. However, on the rarest occasion, this condition can be treated without a cardiac pacemaker. A 56 year old male with a history of chronic kidney disease, was admitted to our emergency department due to the decrease of consciousness. Complete AV block and severe hypotension were detected. Laboratory examination showed severe hyperkalemia and metabolic acidosis. Unexpectedly, the cardiac rhythm was returned into sinus after the serial correction of hyperkalemia using calcium gluconate, insulin, dextrose, and bicarbonate sodium. This case illustrates that hyperkalemia can be a reversible cause of complete AV block, which can be converted into sinus rhythm without a cardiac pacemaker. Routine examination and correction of hyperkalemia can be considered as the alternative initial management before the insertion of the cardiac pacemaker.